2006
DOI: 10.1348/000712605x62768
|View full text |Cite
|
Sign up to set email alerts
|

Training for vigilance: The effect of knowledge of results format and dispositional optimism and pessimism on performance and stress

Abstract: This study investigated the impact of knowledge of results (KR) format on the performance and stress associated with a vigilance task. Also examined was the effect of the interaction of KR-format (Hit-KR, False Alarm-KR, Miss-KR, and a composite of all three formats) with dispositional optimism and pessimism on performance outcome and reported stress state. Hypotheses based upon a theory of feedback intervention were tested. KR regarding correct detections and the composite-KR (KR regarding correct detections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 66 publications
(131 reference statements)
1
61
1
Order By: Relevance
“…Szalma, Hancock, Dember, and Warm (2006) found that providing knowledge of results (KR) during a vigilance task enhanced task engagement; KR may increase participants' attention to their own responses. Parsons, Warm, Nelson, Riley, and Matthews (2007) investigated performance on a task representing the military operation of detecting hostile units.…”
Section: Fatigue Challenge and Perceived Controlmentioning
confidence: 99%
“…Szalma, Hancock, Dember, and Warm (2006) found that providing knowledge of results (KR) during a vigilance task enhanced task engagement; KR may increase participants' attention to their own responses. Parsons, Warm, Nelson, Riley, and Matthews (2007) investigated performance on a task representing the military operation of detecting hostile units.…”
Section: Fatigue Challenge and Perceived Controlmentioning
confidence: 99%
“…This theory suggested that the optimal feedback should direct individuals' attention to the details of a specific task and to learning methods that would help achieve desired results. Based on this logic, letter grades and numerical scores would tend to channel students' attention to the self and away from the task, thus leading to negative effects on performance (Siero & Van Oudenhoven, 1995;Szalma, 2006;Szalma, Hancock, Warm, Dember, & Parsons, in press). Elawar and Corno (1985) looked at their findings through the lens of cognitive theory and research, which emphasized the importance of deep processing when acquiring complex information.…”
Section: Gradingmentioning
confidence: 99%
“…5 Previous deception studies have demonstrated that pacing strategy and performance are largely unaffected by the provision of incorrect performance feedback during self-paced cycling time trials (TT). 6,7 As feedback is most influential when it is attended to and evaluated in respect to salient self-goals, 8 the type of feedback manipulated may have limited the effectiveness of the deceptive interventions. This is further supported by the suggestion that feedback must be mediated by previous experience to influence performance.…”
Section: Introductionmentioning
confidence: 99%
“…23 Participants were informed that their responses should reflect the affective or emotional components of the exercise and not the physical sensations of effort or strain. Borg's 24 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] scale was used to measure RPE and for task-specific self-efficacy, participants reported 'how confident are you to continue at your current pace for the remaining distance of the trial?' on a percentage scale from 0% (cannot do at all) to 100% (absolutely certain can do).…”
mentioning
confidence: 99%